tìm x
a) 35-3IXI=5x(23-4)
b) 10+2IXI=2x(32-1)
a) 35-3IXI=5x(23-4)
b) 10+2IXI=2x(32-1)
bài 1 tìm x
a 12-5x=35:5
b 4-2(1-x)=23:4
\(a,12-5x=35:5\\12-5x=7\\5x=12-7\\5x=5\\x=5:5\\x=1\\b,4-2(1-x)=2^3:4\\\\4-2(1-x)=8:4\\4-2(1-x)=2\\2(1-x)=4-2\\2(1-x)=2\\ 1-x=2:2\\1-x=1\\ x=1-1\\ x=0\)
bài 1/ cho phân số :
A= 2IxI+3/3IxI-1
a) tìm x thuoc Z để A lớn nhất
b) tìm x thuộc Z để A là 1 số tự nhiên
bài 1/ cho phân số :
A= 2IxI+3/3IxI-1
a) tìm x thuoc Z để A lớn nhất
b) tìm x thuộc Z để A là 1 số tự nhiên
bài 1/ cho phân số :
A= 2IxI+3/3IxI-1
a) tìm x thuoc Z để A lớn nhất
b) tìm x thuộc Z để A là 1 số tự nhiên
bài 1/ cho phân số :
A= 2IxI+3/3IxI-1
a) tìm x thuoc Z để A lớn nhất
b) tìm x thuộc Z để A là 1 số tự nhiên
bài 1/ cho phân số :
A= 2IxI+3/3IxI-1
a) tìm x thuoc Z để A lớn nhất
b) tìm x thuộc Z để A là 1 số tự nhiên
Tìm x ϵ N biết :
a) 280 – ( x – 140 ) : 35 = 270 ;
b)( 190 – 2x ) : 35 – 32 = 16;
c) 720 : [ 41 – ( 2x – 5 ) ] = 23 .5
d) ( x : 23 + 45 ) . 37 – 22 = 24 . 105 ;
e) ( 3x – 4 ) . ( x – 1 ) 3 = 0 ;
f) 22x-1 : 4 = 83
g) x17 = x ;
h) ( x – 5 ) 4 = ( x – 5 ) 6 ;
i) ( x + 2 ) 5 = 210 ;
k ) 1 + 2 + 3 + … + x = 78
l) ( 3 .x – 24) . 73 = 2 .74 ;
n) 5x : 52 = 125 ;
m) ( x + 1) 2 = ( x + 1) 0 ;
o) ( 2 + x ) + ( 4 + x ) + ( 6 + x ) + ……+ ( 52 + x ) = 780 ;
p) 70⋮ x , 80 ⋮ x và x > 8
q) x ⋮ 12 , x ⋮ 25 , x ⋮ 30 và 0 < x < 500
bài 1:
a. S2 = 21+23+25+...+1001
b. S4 = 15+25+35+..+115
bài 2:
a. 2x-138= 23 .32
b. 5.(x+35) = 515
c. 814- ( x-305)=712
d. 20 - [ 7(x-3) +4] =2
e. 9x-1 =9
e. 5x-2 -32 = 24 - (28. 22 - 210 . 22)
Bài 1
S₂ = 21 + 23 + 25 + ... + 1001
Số số hạng của S₂:
(1001 - 21) : 2 + 1 = 491
⇒ S₂ = (1001 + 21) . 491 : 2 = 250901
--------
S₄ = 15 + 25 + 35 + ... + 115
Số số hạng của S₄:
(115 - 15) : 10 + 1 = 11
⇒ S₄ = (115 + 15) . 11 : 2 = 715
Bài 2
a) 2x - 138 = 2³.3²
2x - 138 = 8.9
2x - 138 = 72
2x = 72 + 138
2x = 210
x = 210 : 2
x = 105
b) 5.(x + 35) = 515
x + 35 = 515 : 5
x + 35 = 103
x = 103 - 35
x = 78
c) 814 - (x - 305) = 712
x - 305 = 814 - 712
x - 305 = 102
x = 102 + 305
x = 407
d) 20 - [7.(x - 3) + 4] = 2
7(x - 3) + 4 = 20 - 2
7(x - 3) + 4 = 18
7(x - 3) = 18 - 4
7(x - 3) = 14
x - 3 = 14 : 7
x - 3 = 2
x = 2 + 3
x = 5
e) 9ˣ⁻¹ = 9
x - 1 = 1
x = 1 + 1
x = 2
2:
a: \(2x-138=2^3\cdot3^2\)
=>\(2x-138=8\cdot9=72\)
=>2x=138+72=210
=>x=105
b: \(5\cdot\left(x+35\right)=515\)
=>x+35=103
=>x=103-35=68
c: \(814-\left(x-305\right)=712\)
=>x-305=814-712=102
=>x=102+305=407
d: \(20-\left[7\left(x-3\right)+4\right]=2\)
=>7(x-3)+4=18
=>7(x-3)=14
=>x-3=2
=>x=5
e: \(9^{x-1}=9\)
=>x-1=1
=>x=2
f: \(5^{x-2}-3^2=2^4-\left(2^8\cdot2^2-2^{10}\cdot2^2\right)\)
=>\(5^{x-2}-9=16-1024+4096\)
=>\(5^{x-2}=3097\)
=>\(x-2=log_53097\)
=>\(x=2+log_53097\)